Design, Synthesis, and Evaluation of Oleyl-WRH Peptides for siRNA Delivery - Mrigank Shekhar Rai; Muhammad Imran Sajid; Jonathan Moreno; Keykavous Parang; Rakesh Kumar Tiwari (MDPI AG, 2024)
Delivering nucleic acid therapeutics across cell membranes is a significant challenge. Cell-penetrating peptides (CPPs) containing arginine (R), tryptophan (W), and histidine (H) show promise for siRNA delivery. To improve siRNA delivery and silence a model STAT3 gene, we hypothesized that oleyl acylation to CPPs, specifically (WRH)n, would enhance STAT3 silencing efficiency in breast and ovarian cancer cells. Using Fmoc/tBu solid-phase peptide chemistry, we synthesized, purified, and characterized the oleyl-conjugated (WRH)n (n = 1-4) peptides. The peptide/siRNA complexes were non-cytotoxic at N/P 40 (~20 μM) against MDA-MB-231, MCF-7, SK-OV-3, and HEK-293 cells after 72 h incubation. All peptide/siRNA complexes showed serum stability at N/P ≥ 40. The synthesized conjugates, with a diameter of <100 nm, formed nano-complexes with siRNA and exhibited a stable range of zeta potential values (13-18 mV at N/P = 40). Confocal microscopy and flow cytometry analysis provided qualitative and quantitative evidence of a successful cellular internalization of siRNA. The peptides oleyl-(WRH)3 and oleyl-(WRH)4 showed ~60% and ~75% cellular uptake of siRNA, respectively, in both MDA-MB-231 and SK-OV-3 cells. Western blot analysis of oleyl-(WRH)4 demonstrated effective silencing of the STAT-3 gene, with ~75% silencing in MDA-MB-231 cells and ~45% in SK-OV-3 cells.